2013
DOI: 10.25100/cm.v44i3.1248
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported tooth loss and cognitive function: Data from the Hispanic established populations for epidemiologic studies of the elderly (Hispanic EPESE)

Abstract: Objective: To explore the association between tooth loss and cognitive functioning among persons 65 years and older. Methods: Data from the Hispanic Established Populations for Epidemiologic Studies of the Elderly (Wave 1: 1993-1994, n= 3,032; Wave 2: 1995-1996, n= 2,424; and Wave 3: 1998-1999, n= 1,967). The dependent variables were the scores from the total Mini-Mental State Examination (MMSE: score 0-30) and its global domains (memory: score 0-6; and no-memory: score 0-24). Independent variables included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 24 publications
(28 reference statements)
1
70
0
3
Order By: Relevance
“…Hispanic Established Populations for the Epidemiologic Study of the Elderly (HEPESE) study, 9 confirmed that the number of remaining teeth was an indicator of the risk for the onset of cognitive impairment and dementia.…”
Section: And Thementioning
confidence: 81%
See 1 more Smart Citation
“…Hispanic Established Populations for the Epidemiologic Study of the Elderly (HEPESE) study, 9 confirmed that the number of remaining teeth was an indicator of the risk for the onset of cognitive impairment and dementia.…”
Section: And Thementioning
confidence: 81%
“…21 Lastly, we did not record a number of factors that could play a relevant role in cognitive impairment, such as socioeconomic level 22 and malnutrition. 23 Assuming that the preservation of a greater number of teeth entails greater chewing efficacy 24 and that this condition represents a protective factor for cognitive impairment, 9 we can expect that the number of FMUs is as important (or more so) than the number of teeth. Although specific references regarding this issue are scare, a recently published systematic review concluded that elderly individuals have a positive association between chewing and cognitive function, including dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The Hispanic Established Populations Epidemiologic Studies of the Elderly (Hispanic‐EPES) demonstrated that patients with frailty syndrome (prefrailty) and frailty showed significantly lower scores of quality of life in the physical and cognitive domains compared to robust patients. In addition, the study was extended and in a one‐ and 2‐year study, it was found that there is a very large trade‐off between frailty and poor quality of life (Reyes‐Ortiz, Luque, Eriksson, & Soto, ).…”
Section: Discussionmentioning
confidence: 99%
“…The population-based Study of Health in Pomerania, Germany which comprises 1336 subjects (60–79 years) found that, in the fully adjusted models, tooth loss was associated with low MMSE score in females but not in males[ 52 ]. Fewer number of teeth was positively associated with cognitive impairment in the Health, Aging and Body Composition (Health ABC) Study[ 9 ] and the Hispanic Established Populations for Epidemiologic Studies of the Elderly[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral health has been drawn more and more attention on its relationship with cognitive function. In many developed countries, evidence from observational studies suggests that oral heal disorders may be associated with cognitive impairment in community-dwelling older adults[ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, such kind of studies has seldom been conducted in developing countries, such as China.…”
Section: Introductionmentioning
confidence: 99%